Improving the Museum Product - Šola, Tomislav (2003)
The museum product would obviosly be derived from clear definition of the nature role and mission of heritage institution. A step further, a custom-cut museum product made to place heritage institution in the very heart of contemporary demorcatic debate, - not to take sides but to act as corrective, adaptive mechanism of transparency and insight. That is the product so necessery in the issues of human and citizens' rights and in the paramount issues of sustainable development.
Projekt MZOS
ENG